2009
DOI: 10.1016/j.neuron.2009.08.020
|View full text |Cite
|
Sign up to set email alerts
|

CCM2 Mediates Death Signaling by the TrkA Receptor Tyrosine Kinase

Abstract: The TrkA receptor tyrosine kinase is crucial for differentiation and survival of nerve-growth-factor-dependent neurons. Paradoxically, TrkA also induces cell death in pediatric tumor cells of neural origin, via an unknown mechanism. Here, we show that CCM2, a gene product associated with cerebral cavernous malformations, interacts with the juxtamembrane region of TrkA via its phosphotyrosine binding (PTB) domain and mediates TrkA-induced death in diverse cell types. Both the PTB and Karet domains of CCM2 are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 30 publications
2
59
0
1
Order By: Relevance
“…This atypical function of TrkA is still largely unknown and is of keen interest in light of the fact that high expression of TrkA is strongly correlated with positive prognosis in neuroblastoma patients (3). We recently identified the protein product of the cerebral cavernous malformation 2 (CCM2) gene as a cytoplasmic interactor of TrkA that mediates its death effects in neuroblastoma and medulloblastoma (4). CCM2 is one of three genes mutated in patients with cerebral cavernous malformations (CCM), 3 a common class of vascular malformations in the central nervous system (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This atypical function of TrkA is still largely unknown and is of keen interest in light of the fact that high expression of TrkA is strongly correlated with positive prognosis in neuroblastoma patients (3). We recently identified the protein product of the cerebral cavernous malformation 2 (CCM2) gene as a cytoplasmic interactor of TrkA that mediates its death effects in neuroblastoma and medulloblastoma (4). CCM2 is one of three genes mutated in patients with cerebral cavernous malformations (CCM), 3 a common class of vascular malformations in the central nervous system (5).…”
mentioning
confidence: 99%
“…The protein products of these three genes, CCM1, CCM2, and CCM3, interact with each other and with numerous other partners to form a diversity of complexes that may mediate diverse functions in different cell types (6). However, CCM2 was the only CCMrelated gene that could be linked to positive prognosis in neuroblastoma patients, in correlation with TrkA, suggesting that the signaling pathways mediating TrkA-CCM2 death signaling in cells of neural origin might be distinct from the pathways leading to CCM effects on the vasculature (2,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bunun aksine, CCM2 ve TrkA'nın kombine yüksek miktardaki ekspresyonunun nöroblastoma hücrelerini ölüme götürdüğü, hastalarda sağkalım süresini uzattığı gösterilmiştir. Bu bulgular CCM2-TrkA sinyalizasyonunun tümör gerilemesinde spesifik fonksiyonel bir rolü olabileceğini akıllara getirmektedir (34).…”
Section: Sonuçunclassified
“…In many instances, in both primary as well as established MED, NB, and glioblastoma (GB) cell lines, expression of either TrkA or TrkC has been linked to the induction of either apoptosis or autophagy (1,(9)(10)(11)(12). In contrast, we have shown that nerve growth factor (NGF) treatment of MED Daoy cells that overexpress TrkA (Daoy-TrkA) show a dramatic increase in uncontrolled macropinocytosis, causing catastrophic disintegration of cellular membrane integrity, which results in cell death (13).…”
mentioning
confidence: 99%